P PENGARUH TERAPI AL-QURAN SURAH AR-RAHMAN TERHADAP KLIEN RESIKO PERILAKU KEKERASAN - Meti Agustini; Yosra Sigit Pramono (LPPM Universitas Sari Mulia, 2021)
Background: Mental disorders could be experienced by individuals whose coping not properly, resulting in anger that is at risk of violent behavior towards self, others and the environment. Recitation of the Qur'an physically contains elements of the human voice which is an amazing healing instrument and the most accessible tool. Objective: Identifying and analyzing the differences pre and post therapy of Al-Quran Surah Ar-Rahman to clients at risk of violent behavior. Method: this research is Quasi Eksperimen design (pre-post with control group), involved 30 respondents Results: The one way ANOVA test showed that there was an effect of Al-Quran Surah Ar-Rahman therapy on clients at risk of violent behavior with p = 0.000 < (0.05). Conclusion: Al-Quran Surah Ar-Rahman therapy effects on clients at risk of violent behavior.